Mechanical characterization and impact resistance of a novel hybrid composite based on salvadora persica roots and glass fibers - Chetouh, Samir; Ameur, T.; Bouakba, M.; Gaagaia, Djamel Edinne; Khalfi, M.; Safi, Brahim (Zielona Góra: Uniwersytet Zielonogórski)
The observation of fibers in salvadora persica roots inspired us to consider the idea of using them as reinforcement to create an innovative composite. The current work focuses on the volumetric mass density, extraction, molding, and mechanical testing of composites and hybrid composites made from salvadora persica roots and glass fibers reinforced with two types of polyester matrix, chosen due their characteristics suitable for use in different orientations.
Keywords: hybrid composites; natural fibers; glass fibers; tensile strength; impact resistance